Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

The Carnival of Images : Brazilian Television Fiction - Mattelart, Michèle.; Mattelart, Armand. (Bergin & Garvey, 1990)
In creating and developing the new genre of the televised novela, a one-hour long dramatic serial, the Brazilian television industry grew, in less than 15 years, from an insignificant player in the international market to one of the largest, most influential in the world. In the first book in English to explore the phenomenon of the telenovela Michele and Armand Mattelart challenge accepted views of the world dominance of United States television and probe the socioeconomic impact of this new genre on a third world country. Using the telenovela and its impact on the medium world-wide, the authors document the important changes in the international circulation of television programs and in the way television is perceived theoretically as a subject of research. The book traces the development of the novela in a country that, in the early 1960s, did not have any nationwide media and later--from 1964 to the 1970s--was ruled by a military dictatorship. It further analyzes the formation of the genre and its mode of production, placing the novela's appearance and development in its cultural, institutional, and economic context. The authors look at the peculiar contradictory relation between the genre's creators and developers--generally left wing intellectuals--and the manipulations required to construct a television industry in a highly competitive marketplace. The book begins with a description of the economic, institutional, and cultural context which produced the genre. It explores the world of soap operas, the development of a national television industry, and the beginnings of an urban consumer society in Brazil. The authors include a valuable and detailed study of the mode of production of the telenovela, placing both the form and content of the genre in their specific economic and institutional context. The book goes on to examine the relationship between the genre and its wider social and cultural environment, explaining its immense popularity and the social function it fulfills. Finally, the authors link the study of Brazilian television to wider debates in media and cultural studies.
Keywords: 1-TV; 2-Approches sociologiques; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Brésil (corpus analysé); France (lieu de production du savoir); _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Cinema in Expansion: Challenges and Promises of an Intercultural Relationship - Frey, Aline; Brito, Thaís (Canadian Journal of Film Studies, 2020)
Les auteures dressent le portrait tant des défis actuels que des possibilités qui naissent des relations interculturelles se tissant entre commissaires et cinéastes autochtones et non-autochtones dans le cadre du plus grand festival du film autochtone du Brésil, Cine Kurumin. Ce festival annuel, fondé en 2011, se déroule dans des villages ruraux autochtones, de même que dans des métropoles brésiliennes, attirant ainsi des auditoires variés. Le festival est ouvert aux cinéastes autochtones et non-autochtones qui produisent du matériel audiovisuel portant sur des sujets autochtones de partout dans le monde. Divers processus créatifs y sont encouragés grâce à l’organisation d’ateliers de scénarisation, et des partenariats établis avec des chaînes de télévision permettent une plus large diffusion des films sélectionnés. Alors que les productions audiovisuelles autochtones se développent, leurs contenus se diversifient ; elles englobent en effet de plus en plus de thèmes et de styles, de formats et de perspectives variées. En s’appuyant sur un cadre théorique postcolonial et décolonial, les auteures proposent de nouvelles perspectives sur un cinéma en pleine expansion ; les réalisateurs autochtones et leurs films circulent de plus en plus au sein de festivals non thématiques, reçoivent des prix et font rayonner leurs propres voix et points de vue auprès de publics variés, ce qui crée de nombreuses possibilités d’interactions et de dialogues interculturels. En outre, la mise sur pied de Cine Kurumin témoigne du pouvoir des productions audiovisuelles autochtones de générer des relations interculturelles entre cinéastes, commissaires et public.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé